From Happy Wedding to Divorce; Marriage Terms Metaphor in Indonesian Political Coalition - Muhammad Adam; Siti Hafsah (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
: Indonesian political multi-parties system requires political parties to build a solid coalition in anticipating any election event, at all levels; national, regional, and local. The description of the way political parties build the relationship and how candidates seek support from a party is often described metaphorically as stages of marriage. There are few studies of metaphor in political discourse in the Indonesian context, but less attention is given to the detail of the use of the specific source domain MARRIAGE. This study aims to take a deeper look at how the marriage relationship context is used to describe the conceptual metaphor of political coalition establishment. The aim of this study is to identify the mapping principle from the Source domain of MARRIAGE to the target domain POLITICAL COALITION to pinpoint the particular properties that enable characteristics in MARRIAGE to be used as the metaphorical expressions. Conceptual Metaphor Theory (CMT) of Lakoff and Johnson (1980) and Deliberate Metaphor Theory of Steen, (2011) are used as the theoretical framework, with six news headlines about the political coalition from Indonesian online media news is purposively chosen as the data source.